Experiencia pionera en cirugía robótica ginecológica en el Perú: resultados iniciales con el sistema Da Vinci Xi - Clínica Internacional San Borja - Escalante Kanashiro, Guillermo (2025)
Introduction: Robotic-assisted gynecologic surgery offers advantages in submillimetric precision, 3D visualization, and enhanced instrument articulation over conventional laparoscopy. In June 2024, Clínica Internacional San Borja implemented the Da Vinci Xi system, marking the beginning of this technique in Peru. Objectives: To describethe demographic characteristics, diagnoses, intraoperative findings, and surgical outcomes in the initial series of patients undergoing robotic gynecologic surgery.Methods: A retrospective descriptive study was conducted from June to December 2024. Surgical reports and clinical records from 24 patients were analyzed for age, diagnosis, procedure type, operative time, estimated blood loss, and hospital stay.Results: Median age was 41.7 years. The most common diagnosis was uterineleiomyoma (83.3%). A total of 25 procedures were performed, mainly hysterectomies (58.3 %) and myomectomies (33.3 %). Mean operative time was 180.7 minutes, witha mean blood loss of 101 mL. No major complications or conversions occurred. The average hospital stay was 2 days. One patient conceived following robotic surgery.Conclusions: This initial experience with the Da Vinci Xi system supports the safety and effectiveness of robotic gynecologic surgery for complex cases, with satisfactory outcomes and minimal morbidity, advocating for its integration into national clinical practice.